Impact of posterior subcapsular opacification on vision and visual function among subjects undergoing cataract surgery in rural China: Study of Cataract Outcomes and Up-Take of Services (SCOUTS) in the Caring is Hip Project, Report 5 - Congdon, N; Fan, H; Choi, K; Huang, W; Zhang, L; Zhang, S; Liu, K; Hu, I C; Zheng, Z; Lam, D S C (British journal of ophthalmology, 2008)
Aim:To study the effect of posterior capsular opacification (PCO) on vision and visual function in patients undergoing cataract surgery in rural China, and to compare this with the effect of refractive error.Methods:Patients undergoing cataract surgery in at least one eye by local surgeons in a rural setting between 8 August and 31 December 2005 were examined with slit lamp grading of PCO 10–14 months after surgery. Subjects with any PCO associated with best-corrected visual acuity of 6/7.5 or worse, or with grade 2+ or worse PCO without visual decrement, were offered YAG laser capsulotomy. Vision and self-reported visual function were assessed, and various demographic and clinical factors potentially associated with PCO were recorded.Results:Of 313 patients operated on within the study window, 239 (76%) could be contacted by telephone; study examinations were performed on 176 (74%). Examined subjects had a mean (SD) age of 69.4 (10.5) years, 116 (67%) were female, and 149 (86%) had been blind (presenting visual acuity ⩽6/60) in the operated eye before surgery. PCO of grade 1 or above was present in 34 of 204 operated eyes (16.7%). Those with PCO had significantly worse presenting vision (p = 0.007) but not visual function (p>0.3) than those without PCO. Women had a significantly higher prevalence of PCO (20.9%) than did men (8.6%, p<0.05). Of 19 eyes undergoing capsulotomy with best-corrected visual acuity measured the next day, 13 (68%) improved by one or more lines, and seven (37%) improved by two or more lines. Despite a higher uptake of capsulotomy (95%) as opposed to refraction (35%) in this cohort, the yield in terms of eyes with poor presenting visual acuity (<6/18) that could be improved was higher for refraction (26% = 9/35) than for capsulotomy (9% = 3/35).Conclusion:The prevalence of PCO and impact on vision and visual function in this cohort was modest 1 year after surgery. However, PCO prevalence increases with time. Follow-up of this cohort is underway to determine the effectiveness of this early intervention in identifying and treating subjects who will eventually experience clinically significant PCO.